Scrub typhus in winters: A report of two cases from a tertiary care center in sub-himalayan region of the indian subcontinent - Tanya Jain; Vibhu Parcha; Sujeet Raina; Rajesh Sharma (Wolters Kluwer Medknow Publications, 2018)
In India, the geographic variation has been observed while reporting an outbreak of scrub typhus. Our country exhibits seasonality in scrub typhus outbreaks that coincides with the monsoon and postmonsoon period of June-October in Northern regions while it is autumn and early winter from September to January in Southern India. The occurrence of scrub typhus in winter months has not been reported from the sub-Himalayan region of the Indian subcontinent. We report two cases of scrub typhus diagnosed in December and February in a tertiary care center of Himachal Pradesh, India.